The Synergistic Copper Process concept. Issue 4 (2nd October 2018) - Hawker, William; Vaughan, James; Jak, Evgueni; Hayes, Peter C.
ABSTRACT: A new process concept is proposed, one that combines the inherent advantages of conventional hydro- and pyro-metallurgical processes to provide opportunities for significant increases in resource utilisation and smelter productivity. The process involves first leaching copper minerals in aqueous solution, separation of undesirable impurity elements from the solution using conventional hydrometallurgical technologies, and then preparation of a precipitated solid copper compound product. The product can then be used directly as a high-copper, low-iron feedstock in the smelting and/or converting stages of pyrometallurgical copper production. The solid precipitated copper product can be transported to the smelter and used as a separate feed, or can be used to enhance copper concentrations in sulphide concentrate blends. This new tradeable copper product provides an effective way of increasing copper concentrate grades, and the opportunity to more efficiently utilise the excess enthalpy available from the sulphide mineral oxidation reactions in current copper matte smelting and converting process technologies.